High-resolution ultrasound imaging of elementary lesions in dactylitis - Ricci, Vincenzo; Tamborrini, Giorgio; Zunica, Fiammetta; Chang, Ke-Vin; Kara, Murat; Farì, Giacomo; Naňka, Ondřej; Özçakar, Levent (Journal of ultrasound, 2024)
OBJECTIVE: The aim of the present study was to illustrate the (potential) diagnostic role of high resolution US images in assessing the elementary lesions of dactylitis. METHODS: Using high-frequency US machines/probes, we matched the micro-anatomical cadaveric architecture of the digit with multiple sonographic findings of dactylitis. High-sensitive color/power Doppler assessments have also been performed to evaluate the digital microvasculature. DISCUSSION: Modern US equipment/features guarantee prompt and in-depth B-mode and color/power Doppler imaging of tiny anatomical structures of the digit which are usually not properly visible with standard US machines. More specifically, hypervascularization of the digital subcutaneous tissue, fibrous pulleys of flexor tendons, dorsal synovial pads as well as pathological changes of the distal entheseal anchorage network can be accurately detected. CONCLUSION: In clinical practice, high-end US equipment can be used to accurately assess the digits in patients with dactylitis. This way, simple and convenient sonographic diagnosis of different elementary lesions can be timely established.
Keywords: mrtvola; Fingers; Cadaver; Ultrasonography; ultrasonografie; Humans; kloub prstu ruky; mužské pohlaví; prsty ruky; lidé; Male; Ultrasonography, Doppler, Color; Finger Joint; ultrasonografie dopplerovská barevná